The Effectiveness of Rational Emotive Behaviour Therapy Approach Counselling on Students’ Prosocial Behaviour - Wisnu Kurniawan; Sigit Sanyata (Jurnal Pendidikan dan Pengajaran, 2021)
Prosocial behaviour needs to be developed because it is needed to make it easier to interact and establish relationships with others. This study aims to determine the level of effectiveness of group counselling in the Rational Emotive Behaviour (REBT) approach to the improvement of prosocial behaviour in class XI students. This type of research is quantitative with a form of quasi-experimental research. The subjects of the study were 132 students. The instrument used was a scale that contained 51 statement items. Analysis of the data used in this study is the Wilcoxon Signed Rank Test using the help of IBM SPSS v.22. The Wilcoxon Signed Rank Test is used to test the differences and the magnitude of the pre-test and post-test results. This research went through four steps pre-test and post-test to get the results that were wanted. The results of the fourth per-test and post-test revealed that if (p) = 0.018, it was smaller than 0.05 (0.018 <0.05), which means it had a high level of effectiveness, meaning that there were differences in prosocial behaviour before and after group counselling using the Rational Emotive Behaviour (REBT) approach.